2018
DOI: 10.3762/bjoc.14.20
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-flow retro-Diels–Alder reaction: an efficient method for the preparation of pyrimidinone derivatives

Abstract: The syntheses of various pyrimidinones as potentially bioactive products by means of the highly controlled continuous-flow retro-Diels–Alder reaction of condensed pyrimidinone derivatives are presented. Noteworthy, the use of this approach allowed us to rapidly screen a selection of conditions and quickly confirm the viability of preparing the desired pyrimidinones in short reaction times. Yields typically higher than those published earlier using conventional batch or microwave processes were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Introduction of the thioxo group (compounds 8−14) followed the procedure of Xu and Yadan using phenyl thionochloroformate [28]. Compound 8 as well has been described in the literature [29]. The synthesis of the benzothiazole-linker was already described by García-Reyes and Witt et al [15].…”
Section: Synthesis Of New Iwp-based Inhibitor Compoundsmentioning
confidence: 99%
“…Introduction of the thioxo group (compounds 8−14) followed the procedure of Xu and Yadan using phenyl thionochloroformate [28]. Compound 8 as well has been described in the literature [29]. The synthesis of the benzothiazole-linker was already described by García-Reyes and Witt et al [15].…”
Section: Synthesis Of New Iwp-based Inhibitor Compoundsmentioning
confidence: 99%
“…Our previous investigations on the CF rDA reactions of condensed pyrimidinone derivatives revealed that the CF approach is superior to existing conventional batch methods. [9] In this work, starting materials were selected with the aim of testing the viability of the proposed CF rDA protocol with more complex fused pyrimidinone moieties, and also of investigating molecules that have never been subjected to rDA reactions under batch conditions. We started our study with readily available aminocarboxamides 1a-1d, which were prepared by known literature approaches.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that toluene is known to be an effective solvent under superheated CF rDA conditions. [9,33] This effect is even more pronounced when MeOH is used as a cosolvent. The transformation of diexo-methylene-bridged 2-spiroquinazolinone 8 is illustrative.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations